Online Mass Media As Arena of Sultanah Discourse - Gunarto, Wempi (KnE Social Sciences, 2019)
In the year 2015 King of the Kraton Yogyakarta in succession issued Sabda Raja, Dawuh Raja, and Sabdajejering Raja which caused a polemic in Yogyakarta society. Sri Sultan Hamengku Buwono X changed his name to Sri Sultan Hamengku Bawono ka 10 following the accompanying title, has appointed GKR Pembayun, his eldest daughter to be the crown princess with the title of GKR Mangkubumi which is identified as the title of the future male king. The effort of Sultan HB ka 10 wants to smooth his daughter’s step become Sultanah later determined to be the rules applicable in the internal of Kraton Yogyakarta. The group that supports and reject the Sultana discourse also appear in the internal of Kraton Yogyakarta. Both groups are equally using mass media in the network (daring or online) to gain support. Through The Theoretical of Social Practise of Pierre Bourdieu, the author shows how the daring mass media has become an arena to strengthen the sultanah discourse in Kraton Yogyakarta, and the arena has been won by the Disciplinary Supporters of the Sultanah Discourse Keywords: Mass Media, Sultanah Discourse, Contestation, Arenas